Nitrogen-Doped Carbonaceous Materials for Removal of Phenol from Aqueous Solutions. (19th April 2012) - Hofman, Magdalena; Pietrzak, Robert
Abstract : Carbonaceous material (brown coal) modified by pyrolysis, activation, and enrichment in nitrogen, with two different factor reagents, have been used as adsorbent of phenol from liquid phase. Changes in the phenol content in the test solutions were monitored after subsequent intervals of adsorption with selected adsorbents prepared from organic materials. Significant effect of nitrogen present in the adsorbent material on its adsorption capacity was noted. Sorption capacity of these selected materials was found to depend on the time of use, their surface area, and pore distribution. A conformation to the most well-known adsorption isotherm models, Langmuir, and Freundlich ones, confirms the formation of mono- and heterolayer solute (phenol) coverage on the surface of the adsorbent applied herein. The materials proposed as adsorbents of the aqueous solution contaminants were proved effective, which means that the waste materials considered are promising activated carbon precursors for liquid phase adsorbents for the environmental protection.